Effect of a New Imidazolium-based Silver Nanoparticle Irrigant on the Bond Strength of Epoxy Resin Sealer to Root Canal Dentine - Adl, Alireza; Abbaszadegan, Abbas; Gholami, Ahmad; Parvizi, Fateme; Ghahramani, Yasamin (Iranian Endodontic Journal, 2019)
Introduction: The aim of this study was to evaluate the effect of a new imidazolium-based silver nanoparticle (ImSNP) root canal irrigant on the bond strength of AH-Plus sealer to root canal dentine. Methods and Materials: Forty single-rooted extracted human teeth were used in this study. The crowns were resected and according to the irrigation solutions used during root canal preparation, the roots were divided into 5 groups (n=8): Group 1: normal saline (control group), Group 2: 2.5% Sodium Hypochlorite (NaOCl), Group 3: 2.5% NaOCl+17% ethylene diamin tetracetic acid (EDTA), Group 4: silver nanoparticles (AgNPs), Group 5: AgNPs +17% EDTA. After root canal instrumentation, the canals were filled with AH-Plus. Then, after 7 days, 2 or 3 dentine disks were obtained from the mid-root of each sample. Bond strength was measured by the push-out test. Additionally, failure patterns were classified as adhesive, cohesive and mixed. Data were statistically analyzed by one-way ANOVA and Tamhane post hoc tests. The level of significance was set at 0.05. Results: There was no statistically significant differences between groups (P>0.05). Groups 4 (AgNPs), 3 (2.5% NaOCl+17% EDTA) and 2 (2.5% NaOCl) showed statistically higher bond strength compared to group 1 (control group) (P<0.05). Also, Group 4 showed a significant difference with group 5 (AgNPs+17% EDTA) (P=0.017). The failure patterns were mainly cohesive. Conclusion: This in vitro study showed that, when used without EDTA, AgNPs improved the bond strength of AH-Plus to radicular dentine. Keywords: AH-Plus Sealer; Push-out Test; Silver Nanoparticles; Sodium Hypochlorite